The Lives of Native Hawaiian Elders and Their Experiences With Healthcare: A Qualitative Analysis - Keilyn Leina'ala Kawakami; Shelley Muneoka; Rachel L. Burrage; Leslie Tanoue; Kilohana Haitsuka; Kathryn L. Braun (Frontiers Media S.A., 2022)
Native Hawaiians are proud and resilient people who have endured significant impacts from colonization. Despite being in a time of vibrant cultural revitalization, Native Hawaiians have a shorter life expectancy than other racial and ethnic groups in Hawai'i. The primary aim of this paper was to share data from the first year of a 5-year study with Native Hawaiian kūpuna (elders) on their experiences with healthcare, along with barriers to accessing healthcare. Ten kūpuna living in rural areas of Hawai'i participated in three interviews each, which were held in an informal, talk-story style. The first interview focused on establishing rapport. The second interview focused on the kūpuna's strengths, resiliencies, and what they would like to pass to the next generation. The third interview focused on the elders' experiences with healthcare, which is the focus of this paper. All ten kūpuna reported growing up with limited access to Western healthcare; rather, their families successfully treated many illnesses and injuries with lā'au lapa'au (Hawaiian herbal medicine) and other traditional healing practices, as they had done for generations. As Western medicine became more prevalent and accessible, they used both, but many preferred holistic treatments such as prayer, a return to the traditional diet, and lā'au lapa'au. As a group, the kūpuna rated their health as fair to good; two had diabetes, two had cardiovascular disease, four had neuropathies, and five were cancer survivors. The kūpuna reported high turnover among providers in rural communities. Limited access to specialists often required them to travel to Honolulu for care, which was costly and especially difficult during coronavirus disease 2019 (COVID-19). Regardless of provider ethnicity, the kūpuna appreciated those who took the time to get to know them as people and respected Hawaiian cultural practices. They advised that Western providers speak honestly and directly, have compassion, and build connections to patients and their communities.